The role of the United States in the global economy and its evolution over time - Stéphane Dées; Arthur Saint-Guilhem (European Central Bank (ECB), 2009)
This paper aims at assessing the role of the United States in the global economy and its evolution over time. The emergence of large economic players, like China, is likely to have weakened the role of the U.S. economy as a driver of global growth. Based on a Global VAR modelling approach, this paper shows first that the transmission of U.S. cyclical developments to the rest of the world tends to fluctuate over time but remains large overall. Second, although the size of the spill-overs might have decreased in the most recent periods, the effects of changes in U.S. economic activity seem to have become more persistent. Actually, the increasing economic integration at the world level is likely to have fostered second-round and third-market effects, making U.S. cyclical developments more global. Finally, the slightly decreasing role of the U.S. has been accompanied by an increasing importance of third players. Regional integration might have played a significant role by giving more weights to non-U.S. trade partners in the sensitivity of the various economies to their international environment.
Keywords: E32; E37; F41; 330; business cycle; Global VAR; international transmission of shocks; Wirtschaftsintegration; Konjunkturzusammenhang; Makroökonometrie; VAR-Modell; USA; Welt